2022
DOI: 10.1111/rec.13670
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the density and body size of a threatened foundation species across multiple spatial scales

Abstract: Population characteristics (e.g. density and body sizes) of foundation species can affect their own persistence and provisioning of ecosystem functions. Understanding the drivers of population characteristics of foundation species at multiple spatial scales is therefore critical for maximizing ecosystem functions of restored habitats. We analyzed variation in population characteristics (densities, 95th percentile, and median lengths of live oysters) of the Sydney rock oyster, Saccostrea glomerata, on remnant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…Our data also suggest that recruitment is correlated with sedimentation, which may explain the significant differences found among estuaries at most sites. At Crookhaven River, however, recruitment was low despite having low sedimentation, possibly because the unusually strong currents and the higher elevation of the reef surface at this site (Leong et al, 2022) may hinder recruitment, as demonstrated in other studies (e.g., Thomsen & McGlathery, 2006). However, in our study, estuaries with high sedimentation also had longer periods of low salinity and high turbidity (Appendix S1: Table S5).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our data also suggest that recruitment is correlated with sedimentation, which may explain the significant differences found among estuaries at most sites. At Crookhaven River, however, recruitment was low despite having low sedimentation, possibly because the unusually strong currents and the higher elevation of the reef surface at this site (Leong et al, 2022) may hinder recruitment, as demonstrated in other studies (e.g., Thomsen & McGlathery, 2006). However, in our study, estuaries with high sedimentation also had longer periods of low salinity and high turbidity (Appendix S1: Table S5).…”
Section: Discussionsupporting
confidence: 64%
“…To understand the extent to which the habitat attributes of reefs at different scales explained variation in recruitment, following Leong et al (2022), within patches, we quantified surface elevation ("elevation") of each tile and their distances to the nearest reef edge ("dist.to.edge"). Surface elevations were mapped with a Real-Time Kinematic and differential Global Positioning System unit (RTK-dGPS, Leica GNSS 14, vertical accuracy ±8 mm; horizontal ±13 mm), and the distances to patch edges were acquired with XY coordinates of tiles and mapped reef contours (obtained with NearMap) using the "NEARDIST" function (version 10.3, ESRI, 2016).…”
Section: Oyster Recruitment With Habitat Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…McAfee et al 2021 b ) or spatial variability in environmental conditions (e.g. food availability and water quality) that influence oyster performance (Leong et al 2022). Additionally, it remains uncertain what impact the high density of these restored oysters may have on pathogen prevalence (Buss et al 2019), and whether limited parent stock seeding of these reefs may create a genetic bottleneck among the restored population (Reynolds et al 2012).…”
Section: Discussionmentioning
confidence: 99%